Annotirovannıy katalog arhivnıh materialov po buriyatskomu şamanizmu tsentra vostoçnıh rukopisey i ksilografov İnstituta Mongolovedeniya, buddologii i Tibetologii = annotated catalogue of archival materials on buryat shamanism of center of oriental manuscripts and xylographs of the Institute of Mongolian, buddhist, and Tibetan studies (Osaka)
332 s.